Faster healing of radial neck fractures in children treated with the Metaizeau technique compared with percutaneous Kirschner wire fixation: a population-based study - Stöckell, Markus; Lampio, Emmi; Sagstetter, Felicitas; Sinikumpu, Jaakko (BMC musculoskeletal disorders, 2025)
There is increasing experience in the treatment of radial neck fractures using the minimally invasive Metaizeau technique with retrograde elastic stable intramedullary nailing (ESIN) as an alternative to percutaneous Kirschner wire (K-wire) fixation. The main objective of this study was to compare fracture healing between these two techniques. This population-based, single-centre study included all 53 consecutive and eligible patients aged < 16 years with radial neck fractures who were operated on at Oulu University Hospital (OUH), Finland, between 2000 and 2020. OUH is the only 24-hour paediatric trauma centre in the area. Radiographs and characteristics of the injury, patient, treatment and radiographic ossification were reviewed, and the treatment groups were compared. Radiographs were taken until bone healing, and all patients were followed up for potential complications for at least two years (mean 89 months, range 33.0 to 170.5, SD 42.7). All fractures treated with the Metaizeau technique (N = 30) showed complete bone union after 2 months, compared to 18 out of 23 patients treated with K-wire fixation (P = 0.012). There was no difference in final bone union between the treatment groups at the final follow-up visit (P = 0.178). There was also no difference between the groups in overall clinical recovery (P = 0.431), nor in range of motion outcomes, such as pronation (P = 1.000), supination (P = 0.594) or elbow extension-flexion (P = 0.191). The Metaizeau technique more frequently resulted in early bone healing than K-wire fixation. Nevertheless, both techniques resulted in good clinical and radiographic outcomes in the long term, making them viable treatment options. Not applicable.